(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Susatyo P, Lestari W, Sugiharto, Chasanah T. 2022. Reproductive aspects of javaen barb fish, Systomus orphoides in the initial domestication program. Biodiversitas 23: 1511-1519. The population of Javaen barb, Systomus orphoides (Valenciennes, 1842) in the Serayu River Central Java has declined, and domestication is one of the most critical conservation initiatives. This research aimed to evaluate the reproductive aspect of javaen barb, Systomus orphoides in an initial domestication program. Furthermore, fish samples were collected from the Serayu River and reared in traditional ponds. The bred broodstocks were injected with artificial hormones before spawning, and several reproductive aspects were measured and analyzed descriptively according to the literature. Fish specimens had gonadosomatic indexes ranging from 11±0.3% to 16.2±0.9%. The values represented all phases of oogenesis and spermatogenesis in females and males. The reproductive hormone titer consisted of 854.85-1058.06 pg/mL of 17ß estradiol, 0.29-0.72 ng/mL of progesterone, 10.87-15.68 mIU/mL of follicle-stimulating hormone, and 4.18-9.92 ng/mL of testosterone. These findings demonstrated that the Serayu River’s wild Javaen barb population reached all reproductive phases and that broodstocks can be domesticated in the traditional pond.